'We control the engine, we control the world': the geopolitics of gender, nation, and labour in hard-to-place transnational films. Issue 1 (2nd April 2020) - Schwartz, Danielle B.
ABSTRACT: Western academe conceptualizes neoliberalism as a political theory of capitalism's expansion into all facets of being, homogenizing neoliberalism's disparate geopolitical operations on gendered subjects. Transnational film studies attempts an intervention, reclaiming questions of production and authorship alongside consumption and desire, accounting for globalization's shifting landscape. Some scholars call for critical understandings of 'transnational', highlightingpower imbalances in transnational exchanges at sites of production, distribution, and exhibition. Neoliberalism efface gendered, racialized, and nationalized power relations at the site of labour, while arguments in transnational film studies efface geopolitical unevenness in transnational filmmaking and theoretical conceptualizations of the transnational. The industrial circumstances of Slumdog Millionaire and Snowpiercer are ripe for illuminating neoliberalism's uneven gendered effects on divided subjects and nations. Hard to place within clear national borders textually and industrially, these films share precarious positions on global markets geopolitically. A methodology highlighting geopolitical unevenness across industries relationally is necessary for closely attending to sites of reception and stardom beyond the box office, including sites of production, distribution, and text. Examining spatiotemporal formations in these films and their paratexts troubles neoliberalism's emphasis on spatial division. Reading these films from multiple sites proves useful for tracing geopolitical entanglements and particularities of neoliberalism's divergent processes and effects.